Determinants of online trust and their impact on online purchase intention in Yogyakarta - Suprapto, Budi; Wicaksana, Paulus Dian; Mohd Sam, Mohd Fazli (Iran University of Science and Technology, 2022)
Technological developments are very rapidly making changes in consumer behaviour where there is a transition from offline transactions to online in Yogyakarta. The purpose of this study is to evaluate and validate the influence of online trust and the factors that influence it is e-commerce knowledge, perceived reputation, perceived risk, perceived technology, prior purchase experience, to the intention of purchasing online. This study also examines the effect of perceived technology and prior purchase experience on online purchase intentions. Respondents in this study are about 260 respondents. Respondents must be domiciled in Yogyakarta and have conducted online transactions in the last 3 months. Analysis of data on research using Smart PLS 3.0. The test of measurement model that is convergent validity, discriminant validity, and internal consistency reliability is done to ensure the validity and reliability of the questionnaire and then tested the structural model to test the hypothesis, besides the fit model, predictive relevance and effect size of each latent variable. This study found that perceived risk is the most influencing factor of consumer confidence followed by prior purchase experience, perceived technology, and perceived reputation. The study also found that perceived technology and trusts influence online purchase intentions. While e-commerce knowledge has no effect on consumer trust and prior purchase experience has no effect on the intention of purchasing online.